The ANALYSIS OF TIDAL INUNDATION AND THE AGGLOMERATION OF LOSSES IN THE COASTAL AREA OF BONANG SUB-DISTRICT, DEMAK DISTRICT - Adimas Bagus Saputro (Jurnal Geografi : Media Informasi Pengembangan dan Profesi Kegeografian, 2025)
Rob is a disaster whose impact is getting worse due to inappropriate use and management of land in coastal areas, endangering Java's coastal areas which are around 1,000 km long and more than 250 km wide, so that the total area will be threatened. more than 80,000 km of Indonesian coast (Triatmodjo, 1999; Bird and Ongkosongo, 2005). Demak Regency is one of the districts in Central Java which is located on the north coast (Pantura). According to the Demak Regency Central Statistics Agency, settlements in Demak Regency are coastal settlements that are prone to flood disasters, especially in the Bonang District area. The problem of damage due to tides in Demak Province is caused by its geographical location in coastal areas and bordering rivers with almost flat land slopes, and is exacerbated by the reduction in river watersheds due to land conversion. If sea level rise is expected to continue to increase in the long term, there are concerns that flooding due to storms will become more widespread. The impact caused is directly proportional to the area covered by the flood.The method used is a quantitative method with a spatial approach. The research results show that the physiographic conditions of Bonang District, which tend to be flat and have low land elevations, have a significant effect on the area covered by tidal flooding, reaching 71.04% of the total area. With the characteristics of Bonang District as a densely populated area, the resulting estimated losses are even greater. The distance of the moon from the earth also plays a role in determining the height of sea tides, which in turn influences the height of inundation